2013
DOI: 10.3851/imp2612
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Human Papillomavirus Genome Replication for Antiviral Drug Discovery

Abstract: Human papillomavirus (HPV) infections are a major human health problem; they are the cause of recurrent benign warts and of several cancers of the anogenital tract and head and neck region. Although there are two prophylactic HPV vaccines that could, if used universally, prevent as many as two-thirds of HPV-induced cancers, as well as several cytotoxic and immunomodulatory agents for localized treatment of infections, there are currently no HPV antiviral drugs in our arsenal of therapeutic agents. This review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 113 publications
(163 reference statements)
0
18
0
Order By: Relevance
“…This is intriguing as previously the hypothesis was that E2 and Topo1 recruitment and stimulation were parallel and redundant mechanisms (Archambault & Melendy, 2013).…”
Section: Discussionmentioning
confidence: 82%
“…This is intriguing as previously the hypothesis was that E2 and Topo1 recruitment and stimulation were parallel and redundant mechanisms (Archambault & Melendy, 2013).…”
Section: Discussionmentioning
confidence: 82%
“…The major viral oncogenes E6 and E7 target, among other host proteins, p53 and pRb function, respectively, resulting in enhanced proliferation of the infected cell ( 3 ). Two viral proteins are required for replication of the viral genome: E1 and E2 ( 4 ). E2 is a DNA binding protein that forms homodimers and binds to 12-bp palindromic sequences in the LCR surrounding the A/T-rich origin of viral replication ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Topo1 has been previously reported to bind to both PVs E1 and E2 using bacterial protein expression and Southwestern blotting (14,15). These reports suggested that the loading of Topo1 was facilitated by E1, and a replication model was proposed where E1 interacts directly with Topo1 after E2 dissociation (16). However, there have been no in-cell experiments to corroborate these protein-protein interactions or the localization of Topo1 to an active PV ori.…”
Section: Resultsmentioning
confidence: 99%